1982
DOI: 10.1017/s0021859600030069
|View full text |Cite
|
Sign up to set email alerts
|

The influence of irrigation frequency on growth and yield of groundnuts (Arachis hypogaeaL.) under arid conditions

Abstract: A study was carried out for 2 years in the arid zone of the northern region of the Sudan to investigate the effects of watering intervals on flowering, growth, yield and yield components of three groundnut cultivars. The variation in air temperature prevailing above the canopy through frequent and extended watering intervals affected the periodicity of flowering. MH 383 gave the highest pod yield and it was drought tolerant compared with Ashford and Turkish cultivars. Pod losses were smaller with longer wateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This was also pointed out more recently by Reddy et al (2003) in a review. The flowering rate was shown to depend on the frequency of water application and was reduced when water was applied less than once in 6 d (Ishag, 1982). Peg elongation depends on turgor and was shown to be delayed by drought (Boote and Ketring, 1990).…”
mentioning
confidence: 99%
“…This was also pointed out more recently by Reddy et al (2003) in a review. The flowering rate was shown to depend on the frequency of water application and was reduced when water was applied less than once in 6 d (Ishag, 1982). Peg elongation depends on turgor and was shown to be delayed by drought (Boote and Ketring, 1990).…”
mentioning
confidence: 99%
“…Water relations of groundnuts, and their irrigation and water use in the United States, have been comprehensively reviewed by Klepper (1973) and Davidson et al (1973). Water stress reduces yield (Ishag, 1982) and produces pods with a greater aflatoxin content (Pettit et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the phenological stages of peanut that are most sensitive to drought stress are the flowering and pod filling stages (Black et al 1985;Stirling et al 1989;Reddy et al 2003). Ishag (1982) found that irrigation frequency affected the flowering rate, such that less than once irrigation every 6 days caused a reduction in flowering rate. Figure 3 also showed that ET-based water productivity was in a reasonable agreement with cumulative irrigation, with 2008), Pimratch et al (2008) and Tojo Soler et al (2013) also reported that water deficit reduced the total dry matter of different peanut genotypes.…”
mentioning
confidence: 99%